## Beautiful_Lier96 one year ago 1. Find f (g(7)) and g(f(7)) for the functions f (x) = x2 – 3x + 15 and g(x) = –x A. f (g(7)) = 85; g(f(7)) = –43 B. f (g(7)) = –13; g(f(7)) = –8 C. f (g(7)) = –55; g(f(7)) = –27 D. f (g(7)) = –43; g(f(7)) = –43 find the functions that result from f(g(x)) and g(f(x)). 2. f(x)=√2x-1, g(x)=5x+3 A. g(f(x))=√5x+4; f(g(x))=5(√2x-1)+3 B. F(G(X))=√5X+4; G(F(X))=5(√2X-1)+3 C. f(g(x))=√10x+5; g(f(x))=5√(2x-1)+3 D. f(g(x))=√10x-5; g(f(x))=5√(2x-1)-3 3. f(x)=-2x^2, g(x)=x+4 A. f(g(x))=-2x^2-16x-32; g(f(x))=-2x^2+4 B. g(f(x))=-2x^2-16x-32; f(g(x))=-2x^2+4 C. f(g(x))=2x^2+16x+32; g(f(x))=-2x^2+4 D. g(f(x))=2x^2+16x+32; f(g(x))=-2x^2+4

1. ajprincess

to find f(g(x)) plug in g(x) in place of x in f(x). so can u find f(g(x)) for the first question @Beautiful_Lier96

2. Beautiful_Lier96

im still lost -_-

3. GeorgeLavergne

Yeah it's kind of confusing but you need to reread it to understand it a bit more

4. ajprincess

f (x) = x2 – 3x + 15, g(x) = –x . to find f(g(x)) u have to plug in g(x) in stead of x in f(x). f(g(x))=(g(x))^2-3(g(x))+15 =(-x)^2-3(-x)+15 getting this? @Beautiful_Lier96

5. Not the answer you are looking for?
Search for more explanations.

Search OpenStudy